2016
DOI: 10.31219/osf.io/xphfq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confidence Calibration in a Multi-year Geopolitical Forecasting Competition

Abstract: This research examines the development of confidence and accuracy over time in the context of forecasting. Although overconfidence has been studied in many contexts, little research examines its progression over long periods of time or in consequential policy domains. This study employs a unique data set from a geopolitical forecasting tournament spanning three years in which thousands of forecasters predicted the outcomes of hundreds of events. We sought to apply insights from research to structure the que… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
(92 reference statements)
0
3
1
Order By: Relevance
“…We speculate that the most likely cause is a decrease in engagement. We note that this finding is in contrast to that of Mellers et al (2015a), who observed consistent improvements in participant calibration from year to year over the tournament, though they also found that more years of forecasting experience did not correspond to better performance relative to those of less experienced performers (Moore et al, 2015b).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We speculate that the most likely cause is a decrease in engagement. We note that this finding is in contrast to that of Mellers et al (2015a), who observed consistent improvements in participant calibration from year to year over the tournament, though they also found that more years of forecasting experience did not correspond to better performance relative to those of less experienced performers (Moore et al, 2015b).…”
Section: Discussioncontrasting
confidence: 52%
“…Overconfidence (underconfidence) occurs when the observed relative frequency is lower (higher) than the subjective probability. While any increase in a participant's confidence would ideally be matched with an increase in performance, research across many different measures of confidence and performance has found that individuals' subjective confidence is often poorly correlated with their performance (e.g., Aspinall & Cooke, 2013;Griffin & Tversky, 1992;Lichtenstein et al, 1982;Moore et al, 2015b).…”
Section: Confidence Versus Accuracymentioning
confidence: 98%
See 1 more Smart Citation
“…Ideally, any increase in an expert's confidence would be matched with an increase in his or her accuracy or calibration. However, research across many different measures of confidence, accuracy, and calibration has found that these measures are often poorly correlated with one another (e.g., Aspinall & Cooke, ; Griffin & Tversky, ; Lichtenstein et al., ; Moore et al., ).…”
Section: Performance Measures and The Value Of Discussionmentioning
confidence: 99%